VD_FINDINFO HC / 2015 / 422 vom 29. April 2015 - VD Tribunal cantonal (2015)
MINIMUM VITAL, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT | 176 al. 1 ch. 1 CC, 93 LP, 317 al. 1 CPC (CH)